Analysis of the Implementation of Boyolali Regency Regional Regulation Number 4 of 2019 Concerning Food Security Due to the Monkey Population in Kembangsari Village, Musuk District, Boyolali Regency - Laila Isna Rufaida; Burham Pranawa; Ananda Megha Wiedhar Saputri (Regulate: Jurnal Ilmu Pendidikan, Hukum dan Bisnis, 2025)
Food security is a strategic aspect of national development, including in Boyolali Regency, where most of the community depends on the agricultural sector. However, fulfilling food security often faces challenges, one of which is the disturbance caused by long-tailed macaque populations that damage community food crops in Kembangsari Village, Musuk District, thereby threatening local food stability. Regional Regulation of Boyolali Regency Number 4 of 2019 concerning Food Security serves as the legal basis for the regional government in ensuring food availability and accessibility, as well as an instrument for addressing issues that disrupt food production, including pest attacks from monkeys. This research employs an empirical juridical approach with a descriptive qualitative type, using literature study and interviews with the Boyolali Environmental Agency to obtain an overview of the implementation of Regional Regulation No. 4 of 2019 related to food security and the handling of monkey disturbances. The results indicate that the local government has undertaken efforts to control the monkey population through relocation, castration, the release of owls, the installation of physical barriers, and community education. However, the effectiveness of the regulation's implementation remains suboptimal due to limited resources, inter-agency coordination, and the community's level of awareness in supporting the handling programs. Monkey disturbances continue to occur, resulting in decreased crop yields, reduced farmers' income, and hindering household food security. Therefore, an integrated strategy involving local government, BKSDA, and the community is needed to strengthen the implementation of the Food Security Regional Regulation, with measurable technical steps in population control, continuous education, and increased community participation so that the goal of sustainable food security in Kembangsari Village can be achieved optimally.